2018
DOI: 10.1038/s41598-018-22494-4
|View full text |Cite|
|
Sign up to set email alerts
|

Emergence of Different Recombinant Porcine Reproductive and Respiratory Syndrome Viruses, China

Abstract: Epidemiological investigations were conducted on recently emerging porcine reproductive and respiratory syndrome virus (PRRSV) strains in Shandong province in 2014–2015. The proportion of the NADC30 strain identified by ORF7 sequence alignment has been gradually increasing. Three emerging PRRSV strains were successfully isolated, and the complete genomic sequences were determined. Our results indicate the importance of recombinant strains in Shandong province, China. There was a varied degree of recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 45 publications
(60 reference statements)
1
29
0
Order By: Relevance
“…After epidemiological investigations, PRRSV NADC30‐like strain was isolated. Interestingly, we also isolated SS2 from sick pigs infected with PRRSV NAD30‐like strain (Liu et al., ). In this study, we assessed the effect of PRRSV NADC30‐like strain on the invasion and intracellular survival of SS2 in porcine alveolar macrophage (PAM) cells.…”
Section: Introductionmentioning
confidence: 99%
“…After epidemiological investigations, PRRSV NADC30‐like strain was isolated. Interestingly, we also isolated SS2 from sick pigs infected with PRRSV NAD30‐like strain (Liu et al., ). In this study, we assessed the effect of PRRSV NADC30‐like strain on the invasion and intracellular survival of SS2 in porcine alveolar macrophage (PAM) cells.…”
Section: Introductionmentioning
confidence: 99%
“…The co‐existence of different lineages of PRRSV2 not only complicates the control of PRRSV2 infection in China, but also provides a suitable condition for PRRSV recombination in the field. Distinct recombination patterns between/among different lineages of PRRSV2 were observed in the latest reports (Liu et al., ; Zhou et al., ). In this study, we isolated a novel PRRSV2 variant, denominated SD17‐38, in Shandong province of China in 2017.…”
Section: Discussionmentioning
confidence: 79%
“…Moreover, recombination events between HP‐PRRSV and NADC30‐like PRRSV have been frequently reported in recent years (Zhao et al., ; Liu et al., ; Wang et al., ). NADC30‐like PRRSV recombined with VR‐2332‐like and CH‐1a‐like classical PRRSV has also been identified (Li, Ji et al., ; Liu et al., ; Zhou et al., ). A latest study identified a triple recombinant virus SDhz1512 that was recombined from NADC30, classical and HP‐PRRSV isolates (Liu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine reproductive and respiratory syndrome (PRRS) is one of the most important porcine infectious diseases, affecting the global pig industry and leading to significant economic losses each year. Its main symptoms are sow reproductive failure and respiratory disease in pigs of all ages [1,2].The pathogen behind PRRS is PRRS virus (PRRSV), which is an enveloped, single-stranded, positive-sense RNA virus belonging to the genus Arterivirus, family Arteriviridae, order Nidovirales [3,4]. Current vaccination strategies cannot effectively control PRRSV infection due to its unknown viral properties [5][6][7][8] and, as such, there is an imperative need to develop more effective antiviral strategies to combat PRRSV infection.…”
Section: Introductionmentioning
confidence: 99%